2006
DOI: 10.1007/s00024-006-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Element Modeling of Stress and Strain Evolution Within and Outside a Depleting Reservoir

Abstract: Stress changes within and around a depleting petroleum reservoir can lead to reservoir compaction and surface subsidence, affect drilling and productivity of oil wells, and influence seismic waves used for monitoring of reservoir performance. Currently modeling efforts are split into more or less coupled geomechanical (normally linearly elastic), fluid flow, and geophysical simulations. There is evidence (from e.g. induced seismicity) that faults may be triggered or generated as a result of reservoir depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…DEM can therefore be used to study a variety of phenomena characterized by large discontinuous strains on a wide range of scales, in areas from granular flow dynamics to solid rock mechanics. Consequently, DEM is increasingly used to study subsidence problems in civil engineering [e.g., Villard et al , 2009], hydrocarbon exploration [e.g., Alassi et al , 2006] and the mining industry [e.g., O'Connor and Dowding , 1992].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DEM can therefore be used to study a variety of phenomena characterized by large discontinuous strains on a wide range of scales, in areas from granular flow dynamics to solid rock mechanics. Consequently, DEM is increasingly used to study subsidence problems in civil engineering [e.g., Villard et al , 2009], hydrocarbon exploration [e.g., Alassi et al , 2006] and the mining industry [e.g., O'Connor and Dowding , 1992].…”
Section: Methodsmentioning
confidence: 99%
“…We thereby assumed withdrawal of magma out of the plane of section represented in the 2‐D model (i.e., a lateral withdrawal scenario as in the calderas of Figure 1). In this way, we avoided imposing reservoir boundary conditions of constant inward stress [ Alassi et al , 2006] or constant vertical velocity [ Hardy , 2008]. Instead, both reservoir and roof were free to deform under the gravitational loading.…”
Section: Methodsmentioning
confidence: 99%
“…Our synthetic materials could help understand whether simple empirical or theoretical models can effectively describe the relationship between grain size, porosity and compactive yield strength, and thus give accurate predictions for the evolution of inelastic compaction and subsequent subsidence and/or edifice spreading. Moreover, since our synthetic samples consist of a very simplified two‐phase medium, such laws can be easily tested against discrete element method simulations of reservoir compaction (Alassi et al., 2006; Sun et al., 2018a) or volcanic collapses (Harnett et al., 2018) for example.…”
Section: Crustal Implications and Concluding Remarksmentioning
confidence: 99%
“…It is shown that this process zone may have different mechanical properties and permeabilities than the host rock, which could, therefore, lead to stress concentration and affect the permeability evolution during CO2 injection [10][11][12]. Stress and permeability evolution, in and around a fault during reservoir pressure changes, are complex problems, and have been addressed in recent years by several authors [13,14]. There is, however, room for improvement in our understanding of the governing factors such as variation of fault angles and the effect of stress history from reservoir depletion during previous oil and gas production.…”
Section: Introductionmentioning
confidence: 99%